2017
DOI: 10.1242/dev.151282
|View full text |Cite
|
Sign up to set email alerts
|

Tension, contraction and tissue morphogenesis

Abstract: D'Arcy Thompson was a proponent of applying mathematical and physical principles to biological systems, an approach that is becoming increasingly common in developmental biology. Indeed, the recent integration of quantitative experimental data, force measurements and mathematical modeling has changed our understanding of morphogenesis - the shaping of an organism during development. Emerging evidence suggests that the subcellular organization of contractile cytoskeletal networks plays a key role in force gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
154
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(158 citation statements)
references
References 131 publications
3
154
1
Order By: Relevance
“…Whereas the MFM incorporates part of the Hippo pathway, a description of growth also requires the integration of extrinsic growth controls, transduced via the dTOR pathway (Vollmer et al, ). The disk also is mechanically connected to the notum, the basement membrane (Domínguez‐Giménez et al, ; Pastor‐Pareja & Xu, ), apical extracellular matrix (Heer & Martin, ), peripodial cells which are opposed to the disk cells (Baena‐López et al, ), and muscles within the larva (Nienhaus et al, ). As described earlier, recent studies have shown that the basement membrane and the extracellular matrix have significant effects on the overall mechanical properties of the disk (Atzeni et al, ; Keller et al, ).…”
Section: A Model For the Control Of Disk Sizementioning
confidence: 99%
“…Whereas the MFM incorporates part of the Hippo pathway, a description of growth also requires the integration of extrinsic growth controls, transduced via the dTOR pathway (Vollmer et al, ). The disk also is mechanically connected to the notum, the basement membrane (Domínguez‐Giménez et al, ; Pastor‐Pareja & Xu, ), apical extracellular matrix (Heer & Martin, ), peripodial cells which are opposed to the disk cells (Baena‐López et al, ), and muscles within the larva (Nienhaus et al, ). As described earlier, recent studies have shown that the basement membrane and the extracellular matrix have significant effects on the overall mechanical properties of the disk (Atzeni et al, ; Keller et al, ).…”
Section: A Model For the Control Of Disk Sizementioning
confidence: 99%
“…Cells must change shape and move but need to do so without disrupting tissue integrity. These paired needs require integration of the cell adhesion and actomyosin cytoskeletal machinery, which work together to provide cells, tissues, and organs with the correct architecture and allow them to change shape and move in coordinated ways (Heer and Martin, 2017). Epithelial cells, a polarized cell type that act as the building blocks for most tissues, must coordinate adhesion and the cytoskeleton during tissue development.…”
Section: Introductionmentioning
confidence: 99%
“…This common effect suggested that changes in caveola abundance can set levels of tissue tension in monolayers. Changes in cellular contractility are commonly thought to arise when signals such as MLCK and RhoA-ROCK alter the activity of Myosin II (Heer and Martin, 2017). However, neither the level nor activity of 13 Myosin II was detectably changed in CAV1 KD cells.…”
Section: Discussionmentioning
confidence: 99%